Development of reverse phase high-performance liquid chromatographic method for the estimation of HIV non-nucleoside reverse transcriptase inhibitor drug efavirenz in the rat brain - Smita Prakash Kakad; Sanjay Jayprakash Kshirsagar (SpringerOpen, 2021)
Abstract Background The brain is the potential viral reservoir, and estimating the antiviral drug concentration in the brain is a hurdle to the researchers as very few animal models are available for this study. The objective of the study was to develop and validate the RP-HPLC method for the estimation of antiviral drug efavirenz (EFV) in the brain of healthy Wistar rats. EFV was the first-line antiretroviral medication. The optimized HPLC condition used for the analysis had the mobile phase methanol to water (9:1) ratio. The flow rate was set at 0.8 mL/min, while the detection wavelength was 248 nm. Results The retention time was found to be 5.7 min, and the % RSD was found within the limit. Recovery was found to be nearly 78%. The validation results were found to be within the limit range; hence, the obtained method was accurate, specific, rapid, and repeatable for estimation of EFV in the brain. Conclusion This method for estimation of EFV in the rat brain can be applicable for pharmacokinetic and toxicology study of EFV in the brain after administration of EFV to rats. Graphical abstract .